"[S]inne Shalle be no Shame, but Wurshipe to Man": The Role of Chivalry and Chivalric Romance in Julian of Norwich's Soteriology. Issue 2 (17th February 2020) - Prozesky, Maria
ABSTRACT: Julian of Norwich, fourteenth-century English visionary and vernacular theologian, asserts that "sinne shalle be no shame, but wurshipe to man". These opposing concepts of "shame" and "wurshipe" have theological but also chivalric connotations, which I suggest inform the logic of Julian's soteriology. She repeatedly discusses sin within the imaginary of late-medieval chivalry, and at important moments of her argument, Christ becomes a warrior lord and knight, and the Christian salvation narrative a romance adventure in which he risks shame, saves his people, and is rewarded with honour, kingdom and a royal bride. Human sin, similarly, becomes a knightly "assay" or test, the scars of which are "tokens" that mark the soul's membership of Christ's court. Julian's theological originality arises at sites of experimentation in her text, where different literary and theological traditions intersect, suggesting that modern scholarly categories of "secular" and "sacred" need revising when applied to late-medieval English writings.